Penguatan Pendidikan Agama Islam pada Kegiatan Intrakurikuler, Ekstrakurikuler, dan Penciptaan Suasana Religius di Sekolah - Rizki Susanto (Jurnal Pendidikan Islam, 2022)
This paper aims to describe how to strengthen Islamic religious education through intracurricular and extracurricular activities, and the creation of a religious atmosphere in schools. This study uses library research with Miles and Huberman model analysis. The results of the study: first, strengthening PAI through integrated PAI intracurricular activities in learning activities in the initial, core, and closing activities; second, strengthening PAI through PAI extracurricular activities carried out with various activities in the form of daily, weekly and annual activities; and third, strengthening PAI through creating a religious atmosphere is carried out through PAI infrastructure and facilities, Islamic symbolism, and Islamic culture.